International Academy of Cytology Yokohama System for reporting Breast Fine Needle Aspiration Biopsy (FNAB) cytology: A Retrospective Study in a Single South African Tertiary Institution - Pamacheche, Patricia Nee Pariza (Department of Pathology, 2022)
Introduction: Breast carcinoma is the most common malignancy amongst women in South Africa. Triple assessment has been pivotal in the work up and management of breast carcinoma. Breast cytology has been used as a component of the triple assessment. Although core needle biopsy (CNB) is the gold standard and the preferred diagnostic modality, there is still a role for fine needle aspirate cytology (FNAC) in resource limited settings. The present study was conducted at Groote Schuur Hospital in Cape Town, South Africa. Aims: 1. To assess the utility of the International Academy of Cytology (IAC) Yokohama System for Reporting Breast FNAC five category stratifications in our institution. 2. To assess the respective risk of malignancy (ROM) for each category. 3. To assess the diagnostic yield of the breast FNAB at our institution by comparing it to the matched histopathology over a 12-month period. Methodology: A retrospective longitudinal descriptive study was done. A computerized search on TrakCare NHLS for the year 2019, identified 884 patients who had breast cytology and corresponding histology specimens. The cytology categories(C1-C5) were first reclassified according to the IAC Yokohama system. The new cytology category was then compared to the histological diagnosis for each patient. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and risk of malignancy (ROM) were calculated. Results: The sensitivity, specificity, PPV, and NPV were 83.10%, 93.01%, 88.86% and 89.13% respectively. The Cohen's kappa coefficient was 0.659 and percentage agreement was 80.85%. The ROM was calculated; insufficient (9.09%), benign (4.46%), atypia (45.28%), suspicious for malignancy (72.5%) and malignant (91,09%). Conclusion: Breast aspiration cytology performed at GSH has shown good correlation with histopathology as well a high sensitivity and specificity comparable to international standards. The ROM is comparable to previous similar studies. Overall, our results show that breast aspiration cytology is a rapid, accurate and cost-effective diagnostic procedure in our institution that is very useful in the diagnosis of benign and malignant breast lesions.